2020
DOI: 10.1021/acs.chemrev.9b00665
|View full text |Cite
|
Sign up to set email alerts
|

The Staudinger Ligation

Abstract: While the Staudinger reaction has first been described a hundred years ago in 1919, the ligation reaction became one of the most important and efficient bioconjugation techniques in the 1990s and this century. It holds the crucial characteristics for bioorthogonal chemistry: biocompatibility, selectivity, and a rapid and high-yielding turnover for a wide variety of applications. In the past years, it has been used especially in chemical biology for peptide/protein synthesis, posttranslational modifications, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
150
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(162 citation statements)
references
References 365 publications
1
150
0
Order By: Relevance
“…In this synthesis, a modified traceless Staudinger ligation was developed and applied to the stereoselective construction of the sterically cumbersome ( E )/( Z )‐ΔIle residues in solution (Figure 1 b). [21–25] We found that introducing two CF 3 groups and one methoxy group of 9 to the original phosphinophenol structure drastically improved the efficiency of the enamide formation from alkenyl azide 10 . When 9 and 10 were coupled in an aqueous solvent at room temperature, N 2 expulsion, intramolecular amidation from 11 , and release of phosphine oxide 12 proceeded to generate 13 with retention of the original E / Z stereochemistry of 10 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this synthesis, a modified traceless Staudinger ligation was developed and applied to the stereoselective construction of the sterically cumbersome ( E )/( Z )‐ΔIle residues in solution (Figure 1 b). [21–25] We found that introducing two CF 3 groups and one methoxy group of 9 to the original phosphinophenol structure drastically improved the efficiency of the enamide formation from alkenyl azide 10 . When 9 and 10 were coupled in an aqueous solvent at room temperature, N 2 expulsion, intramolecular amidation from 11 , and release of phosphine oxide 12 proceeded to generate 13 with retention of the original E / Z stereochemistry of 10 .…”
Section: Resultsmentioning
confidence: 94%
“…In this synthesis, am odifiedt raceless Staudinger ligationw as developed and applied to the stereoselectivec onstruction of the sterically cumbersome( E)/(Z)-DIle residues in solution (Figure1b). [21][22][23][24][25] We found that intro-ducing two CF 3 groups ando ne methoxy group of 9 to the originalphosphinophenol structure drastically improved the efficiency of the enamide formation from alkenyla zide 10.W hen 9 and 10 werecoupled in an aqueous solvent at room temperature, N 2 expulsion, intramolecular amidation from 11,a nd release of phosphine oxide 12 proceeded to generate 13 with retention of the original E/Z stereochemistryo f10.A dduct 13 was in turn converted to the requisite Fmoc-protected dipeptide 15 by at wo-stepp rotective group manipulation. The three dipeptides with the (E)/(Z)-DIle residues were thus prepared and employed for peptide elongation on resin to attain the solid-phase total synthesis of 1.…”
Section: Resultsmentioning
confidence: 99%
“…While the structure of the aryl azide dictates its reactivity, [33][34][35] functionalised aryl azides have relatively high biological stability, with selective reactivity for strained alkenes and alkynes ([3+2]-cycloadditions), [35][36][37] triphenylphosphines (Staudinger reaction), 38 or H 2 S. [39][40][41] We have developed the alkene-azide [3+2]-cycloaddition as a bioorthogonal click-to-release reaction for prodrugs 28,29,32 and hydrogels, 30,31 while others have investigated H 2 S; a gaseous transmitter in the body, as an activation mechanism for aryl azide-containing probes, prodrugs, and materials. [39][40][41] Alkyl azides can also be reduced by H 2 S 42 or glutathione, 43 however, aryl azides are considered more responsive to, and selective toward, alkenes and H 2 S, 44 even in the presence of other endogenous thiol/thiolate species (e.g., glutathione).…”
mentioning
confidence: 99%
“…[16] The most well-established routes for the formation of amides involve the reactiono fa mines with activated carboxylic acids or their corresponding derivatives, [17] the Schmidt reaction, [18] the Beckmann rearrangement reaction, [19] and modified Staudinger reaction. [20] From the perspective of green chemistry,t hesep rocesses generate al arge amount of byproducts andc hemical waste, so they need to be improved or replaced. Thus, much effort is being devoted to making the formation of amide bonds more "green."…”
Section: Introductionmentioning
confidence: 99%